Proximal Side Optimization: A Modification of the Double Kissing Crush Technique - Francesco Lavarra (Radcliffe Medical Media, 2020)
Coronary bifurcations with significant lesions >10 mm in the side branch (SB) are likely to require two-stent treatment techniques. To date, double kissing Crush (DK-Crush) stenting has demonstrated higher rates of final kissing balloon inflation and better clinical outcomes. The technical iterations that lead to optimal clinical outcomes have been attributed to the first kissing balloon that repairs the distorted proximal segment and fully expands the orifice of the side stent. One potential caution, which relates to all Crush techniques, is the possibility of the guidewire crossing in an inappropriate position toward the Crushed SB stent. When this occurs, the SB stent may be further Crushed, leaving the ostium uncovered, which potentially negates the benefit of the Crush technique. In our experience, proximal side optimization (PSO) during DK-Crush stenting ensures stent size ‘accommodation’ to the larger vessel diameter in the proximal segment and better strut apposition to the wall, which is particularly important in the ostial segment. The benefits of this additional modification of the established DK-Crush technique are reduction or elimination of the risk of SB stent distortion, increase of the space of optimal wiring, and avoidance of guidewire advancement under the stent struts, even in unfavorable anatomies with extreme angulation. The author describes a step-by-step approach of a proposed PSO technique, which is easy to perform without any additional procedural time or costs.